2018
DOI: 10.1038/s41467-017-02408-0
|View full text |Cite
|
Sign up to set email alerts
|

∆133p53 isoform promotes tumour invasion and metastasis via interleukin-6 activation of JAK-STAT and RhoA-ROCK signalling

Abstract: ∆122p53 mice (a model of ∆133p53 isoform) are tumour-prone, have extensive inflammation and elevated serum IL-6. To investigate the role of IL-6 we crossed ∆122p53 mice with IL-6 null mice. Here we show that loss of IL-6 reduced JAK-STAT signalling, tumour incidence and metastasis. We also show that ∆122p53 activates RhoA-ROCK signalling leading to tumour cell invasion, which is IL-6-dependent and can be reduced by inhibition of JAK-STAT and RhoA-ROCK pathways. Similarly, we show that Δ133p53 activates these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 57 publications
3
81
0
Order By: Relevance
“…Increased ∆133p53α isoform expression, in the context of WT TP53, has been associated with poorer disease-free survival in patients with colorectal cancer. A possible mechanism explaining this association is ∆133p53α isoform mediated tumour cell invasion via increased IL-6 expression activating JAK-STAT3 and RhoA-ROCK pathways [77]. Interestingly, in advanced serous ovarian cancer tissue with mutant TP53 gene, ∆133p53α expression was associated with improved disease-free survival and overall survival, providing preliminary evidence that the mutational status of TP53 can influence the association between p53 isoform expression and patients' clinical outcome.…”
Section: Isoforms Studied N Summary Of Key Results Referencesmentioning
confidence: 96%
“…Increased ∆133p53α isoform expression, in the context of WT TP53, has been associated with poorer disease-free survival in patients with colorectal cancer. A possible mechanism explaining this association is ∆133p53α isoform mediated tumour cell invasion via increased IL-6 expression activating JAK-STAT3 and RhoA-ROCK pathways [77]. Interestingly, in advanced serous ovarian cancer tissue with mutant TP53 gene, ∆133p53α expression was associated with improved disease-free survival and overall survival, providing preliminary evidence that the mutational status of TP53 can influence the association between p53 isoform expression and patients' clinical outcome.…”
Section: Isoforms Studied N Summary Of Key Results Referencesmentioning
confidence: 96%
“…Analysis of IIICF/c cells using our long amplicon ddPCR assays clearly detected two t1 transcripts, which was then confirmed by performing splice-aware mapping of the RNA sequencing data. Furthermore, our assays showed that this TP53 splicing mutation led to expression of very high levels of transcripts encoding all ∆133/∆160p53 isoforms, and given the association of some of the ∆133p53 isoforms with invasion and metastasis [12,33], may explain why this mutation is pathogenic.…”
Section: Discussionmentioning
confidence: 75%
“…They share five central exons in common, which span 618 bp, therefore to determine which 5' end and 3' end are part of the same transcript requires amplification of >618 bp. Most PCR-based assays of TP53 transcript abundance, including our own work, have focused on quantifying the individual transcript ends [8][9][10][11][12][13]. These studies have shown that the levels of certain 5' or 3' ends are significantly associated with patient prognosis in a number of cancer types, presumably reflecting the biological functions of the p53 protein sequences encoded by these alternatively-spliced RNA ends.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations